Profile of Superficial Dermatophytosis at the Skin and Venereology Polyclinic of Wulan Windy Hospital Medan for the period 2021-2024 - L.Toruan, Erty Witalaya (CV. Devitara, 2024)
Dermatophytosis is one of the superficial mycoses caused by fungi that invade keratin-containing tissues such as the stratum corneum of the epidermis, hair, and nails. Dermatophytosis is divided based on its location, namely tinea capitis, tinea barbae, tinea cruris, tinea pedis et manum, tinea unguinum, and tinea corporis. Dermatophytosis is caused by dermatophyte fungi from the arthrodermataceae family. This family consists of more than 40 species divided into three genera: Epidermophyton, Microsporum, and Trichophyton. This study aims to determine the profile of dermatophytosis in the Dermatology and Venereology Polyclinic of Wulan Windy Hospital, Medan, from January to December 2013 based on the classification of location, age, gender, occupation, and therapy given. This study is a retrospective descriptive study based on medical record data from new patients who were treated at the Dermatology and Venereology Polyclinic, Wulan Windy Hospital, Medan, in the period 2021-2024. The number of new dermatophytosis patient visits increased from 2021 to 2023, but decreased in 2024. Tinea corporis was the most common diagnosis at 54.9%. Most patients were women. The most common age group found was 45-64 years in 2021-2023. Most treatments were topical. There was an increase in the number of dermatophytosis patients. The most infected age group was the productive age group, because in this age group there was an increase in physical activity and a tendency to sweat a lot and be humid.